2018
DOI: 10.1371/journal.pone.0193833
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoethanolamine-N-methyltransferase is a potential biomarker for the diagnosis of P. knowlesi and P. falciparum malaria

Abstract: BackgroundPlasmodium knowlesi is recognised as the main cause of human malaria in Southeast Asia. The disease is often misdiagnosed as P. falciparum or P. malariae infections by microscopy, and the disease is difficult to eliminate due to its presence in both humans and monkeys. P. knowlesi infections can rapidly cause severe disease and require prompt diagnosis and treatment. No protein biomarker exists for the rapid diagnostic test (RDT) detection of P. knowlesi infections. Plasmodium knowlesi infections can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…Eleven candidates targeted P. falciparum , 10 P. vivax , 2 P. knowlesi , and 2 pan. Phosphoethanolamine N-methyltransferase (PMT) was evaluated for its ability to indicate P. falciparum , P. vivax , and P. knowlesi [ 37 ]. Aldolase (FBPA) made it onto the list of parasite proteins since the article we included in our review identified a P. vivax -specific version of this biomarker [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven candidates targeted P. falciparum , 10 P. vivax , 2 P. knowlesi , and 2 pan. Phosphoethanolamine N-methyltransferase (PMT) was evaluated for its ability to indicate P. falciparum , P. vivax , and P. knowlesi [ 37 ]. Aldolase (FBPA) made it onto the list of parasite proteins since the article we included in our review identified a P. vivax -specific version of this biomarker [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PMT met all but 1: expression by all human-infecting Plasmodium species. A P. malariae orthologue appears to be lacking in PlasmoDB, even though a putative orthologue is predicted to exist [ 37 ]. The studies describing these 3 candidates were classified as early (nonhuman) discovery studies with a level 2 deployability based on the enzyme-linked immunosorbent assay (ELISA) used for detection [ 28 , 37 , 51 ].…”
Section: In Silico Analysis Of P Falciparum Proteomics Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the speci city of the antibodies targeting this epitope would require further analysis. In Krause and Goldring (2018), it was demonstrated that phosphoethanolamine-Nmethyltransferase (PMT) may be able to be used as a target biomarker in malaria RDT [16]. The researchers identi ed PMT epitopes that are speci c to P. knowlesi, P. vivax, and P. falciparum in in silico analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore; the inhibition of catalytic domain of Pf PMT can lead to complete inhibition of SDPM pathway. Since Pf PMT has been found to be expressed throughout the asexual and sexual phases of parasite life cycle and absence of its human orthologues therefore it may be used as target template for development of new antimalarial [1416]. Biochemical studies have demonstrated that human malaria parasite orthologs of PMT have similar structural as well as biochemical properties and inhibition profiles as plasmodium [17].…”
Section: Introductionmentioning
confidence: 99%